ANALYSIS OF INFECTIOUS COMPLICATIONS IN CANCER PATIENTS DURING 2014-2016 - V. V. Aginova; N. V. Dmitrieva; I. N. Petukhova; Z. V. Grigorievskaya; N. S. Bagirova; I. V. Tereshchenko; S. A. Dyakova; T. A. Kalinchuk; A. I. Dmitrieva; V. D. Vinnikova (Сибирский онкологический журнал)
The purpose of the study was to analyze infectious complications caused by multi-drug-resistant organisms depending on anticancer therapy.Material and Methods. A total of 229 cancer patients with infectious complications of cancer therapy were included into the study.Results. Lung cancer was the most predominant cancer (26.6 %) followed by gastric cancer (25.3 %) and esophageal cancer (14.4 %). Infectious complications occurring after surgery were observed in 83.4 % of the patients. Infectious complications caused by Acinetobacter baumannii were the most common (40.6 %), followed by Klebsiella pneumoniae (28.5 %), Pseudomonas aeruginosa (19.5 %), Staphylococcus spp. (9.4 %), and Enterococcus spp. (1.8 %).Conclusion. Infectious complications occurred more frequently in postoperative cancer patients (p<0.02), and the ESKAPE group pathogens were the leading cause of these infections.